Pengaruh Kemandirian Belajar dan Penggunaan Teknologi Terhadap Prestasi Belajar Matematika Selama Pembelajaran Daring Siswa Kelas VI SD Gugus Sinar Harapan - Mayasari, Dian; Prastiti, Tri Dyah; Indriayu, Mintasih (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
The purpose of this study was to (1) analyze the effect of independent learning on mathematics learning achievement during online learning for class VI students. (2) analyzing the effect of using technology on mathematics learning achievement during online learning of class VI students. (3) analyzing the effect of independent learning and the use of technology together on mathematics learning achievement during online learning for class VI students. This research took place in the Sinar Harapan Cluster, Sidoharjo District. The population includes all grade VI students at SD Gugus Sinar Harapan, totaling 7 schools. The sample in this study were 101 students, of which 30 students were for testing research instruments and the remaining 71 students were for research. Data collection techniques with questionnaires. Data analysis technique using multiple linear regression analysis. The results showed that the significance of the effect of independent learning on student achievement was obtained p-value (0.000) <0.05, which means that independent learning (X1) has a positive and significant effect on student achievement (Y). The significance of the effect of the use of technology on student achievement obtained p-value (0.009) <0.05, which means the use of technology (X2) has a positive and significant effect on student achievement (Y). The significance of the influence between learning independence and the use of technology on teacher learning achievement was obtained F count (73.103) > F table (2.70) and a sig value (p-value) of 0.000 <0.05, it can be concluded that there is a simultaneous influence the same between learning independence and the use of technology on student achievement